The Impact of Human Resource Management Policies on Marketing Strategy Implementation: Evidence from Bazian Cement Factory (Raparin Journal of Humanities (RJH), 2025)
This paper examines the connection between Human Resource Management (HRM) policies and the implementation of marketing strategies in the marketing environment of Bazian Cement Factory. In particular, the study examines how Recruitment and Selection, Training and Development, and Performance Appraisal influence the marketing strategy implementation. In order to gather information, a survey was carried out on 200 of the workers in various departments within the factory. Structural equation modeling, or SEM, was used to test the links between the HRM policies and the implementation of the marketing strategies. The findings show that HRM policies play a significant role in the implementation of marketing strategies, and the role of HRM in the development of strategic capabilities of the marketing department is central. Recruitment and Selection, Training and Development, and Performance Appraisal were identified as major predictors, and the coefficients were positive and significant, implying that a better HRM practice is associated with a better implementation of marketing strategies. It is recommended to emphasize the constant enhancement of HRM practices, integrate an approach that would allow aligning HRM policies with the objectives of marketing, and encourage communication between HR and marketing departments. It is also suggested that investment in employee development programs and frequent reviews of HRM policies be made to enhance the synergy between HRM and marketing strategy implementation.